(3OQI GdSdhc ajef Mhi Gdedc ef Gdedhcs - (3GHf GdbGVj , CHh GdYHGS CMeO Hf eMeO Hf eMeO Hf CHj GdYGajI GdecfGSj GdRfGJj, GHf GdbGVj,J (B1025 (3g` s
(3ChdgG (B:s
(3hHYO aGdZQV ef PG GdfXe PcQ CfGS ef edhc Gdbhe s
(3BNQgG (B:s
(3YKeGf Chd edhc GdJQc bO bGhe Gdedc HZjQ Tc s
(3Vef eLehY , JQJjHgG (B: (3ef U (B124 - (3U(B135s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B236 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B147s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B679 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B174 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B((3O (B487) s
Keywords: (3GdJGQjNs